2009
DOI: 10.1177/1933719108330569
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced Hyperlipoproteinemia: Review of the Literature

Abstract: It is well known that with the effect of hormonal changes during pregnancy, plasma lipid levels increase. Expected elevations for triglyceride and cholesterol levels during a normal gestational period usually do not exceed 332 mg/dL and 337 mg/dL, respectively (corresponding 95th percentile values). However, elevations over the 95th percentile values can be observed during pregnancy, and patients with levels over these expected adaptation levels can be divided into 2 groups: (1) supraphysiologic hyperlipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 35 publications
5
105
1
6
Order By: Relevance
“…Biochemical and IHC analysis of the present study revealed the severe OS and the poor antioxidant capacity and thrive for the balance in the antioxidant system in GDM placental tissues. GDM is linked with fetal macrosomia [42], endothelial dysfunction associated with dyslipidemia, also known as hypertriglyceridemia, a positive correlation between maternal triglycerides and neonatal body weight [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and IHC analysis of the present study revealed the severe OS and the poor antioxidant capacity and thrive for the balance in the antioxidant system in GDM placental tissues. GDM is linked with fetal macrosomia [42], endothelial dysfunction associated with dyslipidemia, also known as hypertriglyceridemia, a positive correlation between maternal triglycerides and neonatal body weight [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Basarán (29), sugiere que durante un período de gestación normal, los niveles de CT y TG no deben superar 337 mg/dl y 332 mg/dl respectivamente. En este trabajo se obtuvieron valores de percentilo 95 para CT y TG de 321 mg/dl y 371 mg/dl respectivamente, correspondientes al tercer trimestre, los cuales podrían ser utilizados como valores de corte en nuestra población.…”
Section: Discussionunclassified
“…Progesterone-Mediated Reductions in Cholesterol During Pregnancy, the Luteal Phase, and Menopause Early pregnancy is associated with a nadir in the mean value of serum cholesterol (Darmady and Postle 1982;Basaran 2009). Although cholesterol rises steadily through gestation, early in the first trimester there is an initial decrease in plasma lipids (Basaran 2009;Sep et al 2011).…”
Section: The Functions Of Cholesterol Andmentioning
confidence: 99%
“…Although cholesterol rises steadily through gestation, early in the first trimester there is an initial decrease in plasma lipids (Basaran 2009;Sep et al 2011). Cholesterol levels eventually climb dramatically, but recovery from the initial decline is gradual, such that LDL levels at the end of the first trimester are often still within normal ranges (Brizzi et al 1999); it is generally only by the beginning of the second trimester that cholesterol levels rise substantially above the pre-pregnancy baseline (Basaran 2009). …”
Section: The Functions Of Cholesterol Andmentioning
confidence: 99%
See 1 more Smart Citation